Pengaruh Konsumsi Minuman dengan Kandungan Gula Tinggi dan Aktivitas Fisik Terhadap Status Gizi pada Remaja - Alifa Syifa Salsabilah Prastowo; Dian Widiyanti; Afrizal Tw; Sri Wuryanti (Jurnal Sosial Teknologi, 2026)
Sugar-sweetened beverages (SSBs) are increasingly popular among adolescents and contribute significantly to daily caloric intake, potentially affecting nutritional status. This study aims to analyze the effect of high-sugar beverage consumption and physical activity on nutritional status among adolescents. This cross-sectional study involved 90 junior high school students aged 12-15 years from two schools selected proportionally. Data were collected using the BEVQ-15 questionnaire for high-sugar beverage consumption, IPAQ for physical activity, and direct measurements of weight and height to determine nutritional status based on BMI. Data analysis used Chi-Square test for bivariate analysis and ordinal regression for multivariate analysis. Results showed that the majority of respondents (66.7%) had low consumption of high-sugar beverages. Distribution of nutritional status showed most respondents were in the underweight category and normal nutritional status. Bivariate and multivariate analysis showed no significant relationship and effect between high-sugar beverage consumption and physical activity on adolescent nutritional status (p > 0.05). This study concludes that high-sugar beverage consumption and physical activity showed no significant effect on adolescent nutritional status, possibly due to uneven distribution of nutritional status and the influence of other unmeasured factors such as total energy intake, overall dietary patterns, and genetic factors.